How and why do women's groups (WGs) improve the quality of maternal and child health (MCH) care? A systematic review of the literature. Issue 2 (21st February 2022) - Canuto, Karla; Preston, Robyn; Rannard, Sam; Felton-Busch, Catrina; Geia, Lynore; Yeomans, Lee; Turner, Nalita; Thompson, Quitaysha; Carlisle, Karen; Evans, Rebecca; Passey, Megan; Larkins, Sarah; et al.
Abstract : Background: This systematic review was undertaken to assist the implementation of the WOmen's action for Mums and Bubs (WOMB) project which explores Aboriginal and Torres Strait Islander community women's group (WG) action to improve maternal and child health (MCH) outcomes. There is now considerable international evidence that WGs improve MCH outcomes, and we were interested in understanding how and why this occurs. The following questions guided the review: (1) What are the characteristics, contextual influences and group processes associated with the MCH outcomes of WGs? (2) What are the theoretical and conceptual approaches to WGs? (3) What are the implications likely to inform Aboriginal and Torres Strait Islander WGs? Methods: We systematically searched electronic databases (MEDLINE (Ovid); CINAHL (Ebsco); Informit health suite, Scopus, Emcare (Ovid) and the Cochrane Library and Informit), online search registers and grey literature using the terms mother, child, group, participatory and community and their variations during all time periods to January 2021. The inclusion criteria were: (1) Population: studies involving community WGs in any country. (2) Intervention: a program/intervention involving any aspect of community WGs planning, acting, learning and reviewing MCH improvements. (3) Outcome: studies with WGs reported a component of: (i) MCH outcomes; or (ii) improvements in the quality of MCH care or (iii) improvements in socioemotional well-being of mothers and/or children. (4) Context: the primary focus of initiatives must be in community-based or primary health care settings. (5) Process: includes some description of the process of WGs or any factors influencing the process. (6) Language: English. (7) Study design: all types of quantitative and qualitative study designs involving primary research and data collection. Data were extracted under 14 headings and a narrative synthesis identified group characteristics and analysed the conceptual approach to community participation, the use of theory and group processes. An Australian typology of community participation, concepts from Aboriginal and Torres Strait Islander group work and an adapted framework of Cohen and Uphoff were used to synthesise results. Risk of bias was assessed using Joanna Briggs Institute Critical Appraisal Tools. Results: Thirty-five (35) documents were included with studies conducted in 19 countries. Fifteen WGs used participatory learning and action cycles and the remainder used cultural learning, community development or group health education. Group activities, structure and who facilitated groups was usually identified. Intergroup relationships and decision-making were less often described as were important concepts from an Aboriginal or Torres Strait Islander perspective (the primacy of culture, relationships and respect). All but two documents used an explicit theoretical approach. Using the typology of community participation, WGs were identified as predominantly developmental (22), instrumental (10), empowerment (2) and one was unclear. Discussion: A framework to categorise links between contextual factors operating at micro, meso and macro levels, group processes and MCH improvements is required. Currently, despite a wealth of information about WGs, it was difficult to determine the methods through which they achieved their outcomes. This review adds to existing systematic reviews about the functioning of WGs in MCH improvement in that it covers WGs in both high-income and low-income settings, identifies the theory underpinning the WGs and classifies the conceptual approach to participation. It also introduces an Australian Indigenous perspective into analysis of WGs used to improve MCH. PROSPERO registration number: CRD42019126533.